2021
DOI: 10.1200/po.21.00162
|View full text |Cite
|
Sign up to set email alerts
|

Integrating 31-Gene Expression Profiling With Clinicopathologic Features to Optimize Cutaneous Melanoma Sentinel Lymph Node Metastasis Prediction

Abstract: PURPOSE National guidelines recommend sentinel lymph node biopsy (SLNB) be offered to patients with > 10% likelihood of sentinel lymph node (SLN) positivity. On the other hand, guidelines do not recommend SLNB for patients with T1a tumors without high-risk features who have < 5% likelihood of a positive SLN. However, the decision to perform SLNB is less certain for patients with higher-risk T1 melanomas in which a positive node is expected 5%-10% of the time. We hypothesized that integrating clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The 10-GEP test was used to identify patients with primary cutaneous melanoma at low risk for nodal metastases (Table 1) [42,61]. The 31-GEP test is primarily useful for risk stratification in patients with early-stage melanoma, where individuals who might benefit from heightened surveillance and closer followup (even though they may have previously been designated as being low risk) are identified (Table 1) [62][63][64][65][66][67][68][69].…”
Section: -Gep and 35-gep Testing: Pathology Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The 10-GEP test was used to identify patients with primary cutaneous melanoma at low risk for nodal metastases (Table 1) [42,61]. The 31-GEP test is primarily useful for risk stratification in patients with early-stage melanoma, where individuals who might benefit from heightened surveillance and closer followup (even though they may have previously been designated as being low risk) are identified (Table 1) [62][63][64][65][66][67][68][69].…”
Section: -Gep and 35-gep Testing: Pathology Diagnosismentioning
confidence: 99%
“…There are four categories: class 1A (0 to 0.41, lowest risk), class 1B (0.42 to 0.49, low risk), class 2A (0.50 to 0.58, high risk), and class 2B (0.59 to 1, highest risk). Hence, lesions that are either class 1B or class 2A are considered to present increased (or intermediate) risk [62][63][64][65][66][67][68][69].…”
Section: -Gep and 35-gep Testing: Pathology Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] The 31-GEP continuous risk score has been integrated with clinical and pathological features (Breslow thickness, mitotic rate, ulceration, and age) using a neural network algorithm to determine a precise risk score for SLN positivity (i31-GEP SLNB) and the 31-GEP score was a significant and independent contributor. 12 The i31-GEP algorithm for SLNB was shown to provide benefit for selecting patients for SLNB over treating all with SLNB. 13 This test also provides each patient with their personalized risk of SLN metastasis rather than binning patients as high or low risk, which may miss the nuances associated with each patient's specific tumor, and, ultimately, preclude opportunities for shared decision-making between the patient and clinician.…”
mentioning
confidence: 99%
“…Recently, we described the development of a novel neural network algorithm (i31-SLNB) that integrates the continuous 31-GEP test result with MR, age, ulceration, and Breslow thickness for a personalized and precise risk of SLN positivity. 10 The algorithm was developed on a cohort of 1398 patients and independently validated in 1674 patients with Stage I-III melanoma. We analyzed SLNB reduction rates in each T-stage and found that in patients with T1b tumors, the i31-SLNB predicted that 40.9% of patients had a <5% risk of SLN positivity.…”
mentioning
confidence: 99%